Demographic, Clinical Profile and Outcomes of Neonates Admitted to Neonatal Intensive Care Unit of Dekemhare Hospital, Eritrea - Hailemichael Gebremariam; Berhe Tesfai; Seltene Tewelde; Samsom Abay; Danait Tekeste; Fitsum Kibreab (BMC, 2022)
Abstract Background Ninety-six percent of the world's 3 million neonatal deaths occur in developing countries where the majority of births occur outside health facility. The objective of this study was to evaluate the demographic, clinical profile and outcome of neonates admitted to Neonatal Intensive Care Unit of Dekemhare Hospital of Eritrea. Methods The study was a retrospective register-based review of all neonates admitted from January 2018 to December 2021 to Dekemhare Hospital. Overall, 509 neonates were enrolled in this study. Data were collected from neonatal register book from January 5 to February 5, 2022 by general practitioners using a predesigned data collection tool. Data entry was done using CSpro 7.3 and analyzed through SPSS version 22. Results were presented in frequencies, percent and odds ratio. Univariable and multivariable analysis was done to measure the association between the variables. Results Three quarter (75.6%) of the neonates had normal birth weight and 80.0% were term. Majority (75.4%) of the neonates was delivered vaginally and 92.7% were delivered at health facility. Neonatal infection (33.0%), birth asphyxia (20%) and prematurity (14.3%) were the top three primary causes of neonatal admission to the Neonatal Intensive Care Unit. Furthermore, 31% of neonatal deaths occurred during 24-72 hours of their life and the mortality rate was 16.3%. Multivariable analysis indicated that low birth weight (AOR: 7.28; 95%CI: 2.85-18.55) increased neonatal mortality. Whereas delivery at health facility (AOR: 0.17; 95%CI: 0.06-0.47), hospital stay 4-7 days (AOR: 0.06; 95% CI: 0.02-0.23) and above 8 days (AOR: 0.06; 95%CI: 0.02-0.23) were showing protective effect on neonatal mortality. Conclusion Congenital abnormality, prematurity and birth asphyxia had higher case fatality rate. And, low birth weight, delivery at health facility and hospital stay were found to be predictors of neonatal mortality. Training of health professionals on neonatal resuscitation, further improvement on the diagnostic setup, treatment tools, infrastructure and raising community awareness to deliver at health facility are crucial to decrease the neonatal mortality in Eritrea.